Risks and Opportunities of Participation in Global Value Chains - Gereffi, Gary; Luo, Xubei (World Bank, Washington, DC, 2014)
This is a background paper to the 2014 World Development Report. Risk is inherent to the pursuit of opportunity. This paper surveys the recent literature and looks at the risks and opportunities firms and their workers face in the global value chains. First, it examines the risk-sharing mechanisms that firms provide from the national and global perspectives; second, it takes a closer look at the new opportunities and challenges for firms and individuals in the global arena; third, it discusses the role of economic upgrading and social upgrading; and finally it sheds light on how the government can help people manage risks and reap the benefits in the participation of global value chains.